Long-chain noncoding RNA NEAT1 and autoimmune diseases - Cheng Bao; Li-Li Tian; Xiao-Liu Li; Min Xu; Hong-Wei Chen (Exploration of Immunology)
Autoimmune diseases result from the immune system’s response to autoantigen components, leading to damage to one’s own tissues and organs. The correlation between long noncoding RNAs (lncRNAs) and autoimmune diseases remains inconclusive. However, recent studies have revealed that the lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) plays a vital role in the development of various autoimmune diseases. Here, this review briefly summarizes the progress in understanding NEAT1 expression variations and related mechanisms in different autoimmune diseases, and discusses its potential use for future therapeutic applications.